2002
DOI: 10.1126/science.1072086
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Organization of Single CdTe Nanoparticles into Luminescent Nanowires

Abstract: Nanoparticles of CdTe were found to spontaneously reorganize into crystalline nanowires upon controlled removal of the protective shell of organic stabilizer. The intermediate step in the nanowire formation was found to be pearl-necklace aggregates. Strong dipole-dipole interaction is believed to be the driving force of nanoparticle self-organization. The linear aggregates subsequently recrystallized into nanowires whose diameter was determined by the diameter of the nanoparticles. The produced nanowires have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

78
1,855
15
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,838 publications
(1,956 citation statements)
references
References 20 publications
78
1,855
15
8
Order By: Relevance
“…7 Assuming a 3.1 nm interparticle separation (from our own measurements on CdSe NCs), eq 4 yields an upper estimate of ∼-0.6 k B T at room temperature for the interparticle interaction if the dipole moment is 100 D. This interaction is too small to account for the anisotropic nanocrystals grown via oriented attachment. 1,3,4 As is demonstrated by Figure 1, for strong dipolar interactions, large aggregates are expected at high concentrations with a highly one-dimensional character. With magnetic colloids that form magnetic equilibrium structures according to cryo-TEM, it has been demonstrated that the response to an alternating field occurs at frequencies corresponding to the (slow) rotation of the dipolar structures.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…7 Assuming a 3.1 nm interparticle separation (from our own measurements on CdSe NCs), eq 4 yields an upper estimate of ∼-0.6 k B T at room temperature for the interparticle interaction if the dipole moment is 100 D. This interaction is too small to account for the anisotropic nanocrystals grown via oriented attachment. 1,3,4 As is demonstrated by Figure 1, for strong dipolar interactions, large aggregates are expected at high concentrations with a highly one-dimensional character. With magnetic colloids that form magnetic equilibrium structures according to cryo-TEM, it has been demonstrated that the response to an alternating field occurs at frequencies corresponding to the (slow) rotation of the dipolar structures.…”
mentioning
confidence: 68%
“…[1][2][3][4] An example is the growth of single-crystalline nanowires from PbSe NCs, which indicates that the particles attach to each other in a precise orientation. 3 The origin of the underlying directive force observed for various types of nanocrystals is still under debate.…”
mentioning
confidence: 99%
“…51 This dipole−dipole attraction between particles was strong enough to drive the aggregation of nanoparticles. 52 The aggregation of small AgNPs and further reduction Ag + to Ag 0 could induce the fusion and growth of nanoparticles and result in formation of larger AgNPs. Therefore, the photo-and heat-induced AgNPs result in varying size-distribution patterns.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One-dimensional nanowires [2] and twodimensional free-floating sheets have been developed by strong dipole-dipole interaction [3]. To structure matter on the scale of length comparable or smaller to the wavelength of light can deliver phenomenal optical properties [4,5].…”
Section: Last and Final Versionmentioning
confidence: 99%